Effect of Benzylaminopurine (BAP) and Coconut Water on the Growth of Bucephalandra sp. in Vitro - Septianingsih, Alfira Damayanti; Makhziah, Makhziah; Sukendah, Sukendah (The University of Lampung, 2024)
Tissue culture is useful as a way to obtain seeds in large quantities of seedlings in a short time as an effort to preserve Bucephalandra sp. in nature. The use of PGR has problems such as expensive prices and difficult to find, therefore its use can be replaced by natural PGR that are easy to obtain and have relatively cheap prices such as coconut water. The aim of this research was to determine the effect of Benzylaminopurine (BAP) and coconut water on the growth of Bucephalandra sp. in vitro. This research is a 2-factor factorial experiment using a completely randomized design. The factors are concentration of BAP (0; 1; 3; 5 mg/l) and concentration of coconut water (0; 50; 100 ml/l). The results showed Murashige and Skoog (MS) media with the addition of BAP 1 mg/l + coconut water 50 ml/l (4.11 shoots), BAP 5 mg/l + coconut water 50 ml/l (4.33 shoots), and BAP 3 mg/l (6.22 shoots) were able to provide the number of shoots with high results. The addition of coconut water did not affect the growth of Bucephalandra sp. MS media can grow shoots with the best results in measurements of shoot emergence time, number of roots, shoot and root length. Keywords: Aquatic plant, Endemic plant, Plant growth regulators, Tissue culture.